Analisis Sistem Kerja untuk Meningkatkan Produktivitas Pegawai Negeri Sipil dengan Pendekatan Macroergonomic Analysis and Design - Delvieri Salsa Bella Putri; Wahyudin Wahyudin; Hamdani Hamdani (Jurnal Serambi Engineering, 2021)
The productivity of a job is influenced by many things, one of which is the work system. To get optimal productivity, it is necessary to design a good work system. A good work system at least provides security and comfort to workers when carrying out their work. Thus, workers can do work more actively and achieve the targets that have been set previously. This research is applied in the Community and Village Empowerment Service (DPMD) especially in the general and staffing sub-sections. The purpose of this study is to identify the work system applied to the DPMD, and evaluate the work system in order to get better conditions to increase productivity. The method of data analysis is using macroergonomy approach namely MEAD which is used in analyzing and evaluating work systems with structured and systematic steps. From the results obtained, it is known that the work system implemented by the DPMD has been running effectively and efficiently in accordance with the established vision and mission. While the factors that affect productivity are the physical environment, work equipment, working conditions, and organizational systems. From the calculation of % HR Reserve and Cardiovascular Load (% CVL) the value is 56.34% while the rest time is -0.083. From these results, it is known that the rest time given is sufficient and there is no need for additional rest periods.